ESTIMATION OF HIGHLY SENSITIVE TROPONIN TESTS IN THE DIAGNOSIS OF ACUTE CORONARY SYNDROME - L. V. Kremneva; S. N. Suplotov; S. V. Shalaev (Рациональная фармакотерапия в кардиологии)
Review is devoted to the value of the use of highly sensitive troponin (hs-cTn) tests in the diagnosis of acute coronary syndrome. The classification of the Tn-tests depending on their sensitivity is presented. The possible reasons of troponins appearance in blood of healthy people are shown. Authors consider a 3-hour algorithm for myocardial infarction (MI) diagnostic, recommended by the expert group in 2012. Study results of 2011-2015 years are presented as the basis for the development of a one-hour MI diagnostic algorithm, recommended by the European Society of Cardiology in 2015. Authors discuss the results of studies showing that modern HS-cTnt tests (together with ECG assessment) are capable to diagnose MI in the early stages. They significantly increase the number of identified MI, especially MI without ST segment elevation, as well as identify the group of patients with subsequent favorable prognosis.